The Role of Muslimat Al-Washliyah in Medan City in Strengthening Family Based Islamic Education - Hayatsyah Hayatsyah (Al-Fikru: Jurnal Ilmiah, 2025)
The weakening of family-based Islamic education due to social change, digital media penetration, and limited parental capacity necessitates the involvement of socio-religious actors at the community level. In this context, Islamic women’s organizations play a strategic role in strengthening family-based Islamic education. This study aims to analyze the role of the Regional Administrator of Muslimat Al-Washliyah in Medan in fostering religious values, moral development, and worship practices within the household. The study employs a qualitative approach with a case study design. Data were collected through in-depth interviews with organizational leaders and members, observations of religious gatherings and Islamic parenting programs, and analysis of organizational documents. Data analysis was conducted inductively through data reduction, data display, and conclusion drawing, with triangulation used to ensure data credibility. The findings indicate that the Regional Administrator of Muslimat Al-Washliyah in Medan performs educational, socio-religious, and women empowerment roles in strengthening family-based Islamic education. These findings imply the importance of reinforcing the role of Islamic women’s organizations as strategic partners in developing contextual and sustainable family-based Islamic education policies and practices.